Integrasi Teknologi Kecerdasan Buatan dalam Khotbah: Tinjauan terhadap Etika dan Kepantasan - Purwonugroho, Daniel Pesah; Ekoliesanto, Yesaya Bangun (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
Preaching is a form of Christian ministry in which a preacher delivers the message of God's Word. The role of preaching is central in Christian ministry. The preaching role can influence the character of individuals or congregations. In this modern era, the role of preaching has been replaced by the sophistication of artificial intelligence where the use of artificial intelligence to deliver the Word of God has occurred in Germany. The use of artificial intelligence is made possible because artificial intelligence is able to replicate human intelligence and make decisions as well as explore various religious-related information in delivering the Word. However, ethically, the use of artificial intelligence results in the drying up of human spiritual experience. The use of artificial intelligence in delivering the Word replaces humans cannot bring about spiritual growth. Through a descriptive qualitative approach, the author attempts to describe the concept of preaching according to the Bible. The author also describes the sophistication of artificial intelligence. The author will examine this from ethical and appropriateness perspectives. The author states that the role of AI replacing humans in preaching is inappropriate and unethical. It is humans who should deliver the message of God's Word.